High molecular weight anionic polyacrylamide

Anionic polymer P2 was prepared in the salt form of the anionic monomer 2-acrylamido-2-methylpropanesulfonic acid, and P1 homopolymer was added. This solved the problems of dissolution and free radical degradation resistance of anionic polyacrylamide in the prior art, improved its efficiency and filterability in oil and gas extraction and hydraulic fracturing, and reduced production costs.

CN117946311BActive Publication Date: 2026-11-06SNF CHINA FLOCCULANT
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202211275522.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2026-11-06
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

Existing high molecular weight anionic polyacrylamide has problems with dissolution and resistance to free radical degradation, resulting in low efficiency in oil and gas extraction and hydraulic fracturing. It also has poor filterability, which can easily clog formations, increasing production costs and difficulties.

Method used

Anionic polymer P2 was prepared by salt formation of the anionic monomer 2-acrylamido-2-methylpropanesulfonic acid. An anionic water-soluble homopolymer P1 was added to improve its solubility and resistance to free radical degradation, forming a polymer composition to improve filtration and viscoelastic properties.

Benefits of technology

It enables rapid dissolution of polymers, reduces equipment requirements, lowers carbon footprint, improves polymer lifespan and filterability, and is suitable for enhanced oil and gas recovery and hydraulic fracturing, while also enhancing proppant suspension and fracture retention capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003896386530000121
    Figure BDA0003896386530000121
  • Figure BDA0003896386530000181
    Figure BDA0003896386530000181
  • Figure BDA0003896386530000182
    Figure BDA0003896386530000182
Patent Text Reader

Abstract

The present invention relates to a polymer composition comprising a water-soluble anionic P2 polymer obtained by free-radical polymerization of at least one anionic monomer in the presence of a water-soluble homopolymer P1 having a weight average molecular weight of 5,000 to 100,000 Dalton, the water-soluble anionic P2 polymer having a weight average molecular weight greater than 100,000 Dalton and less than or equal to 40 million Dalton, the water-soluble P1 homopolymer being prepared from 2-acrylamido-2-methylpropanesulfonic acid in salt form in the presence of 200 to 20,000 ppm by weight of 2-methyl-2-propenylsulfonic acid in salt form.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to high molecular weight anionic polyacrylamides. More specifically, these anionic polyacrylamides are obtained by polymerization of anionic monomers in the presence of a homopolymer of 2-acrylamido-2-methylpropanesulfonic acid in a salt-forming form with a weight average molecular weight of 5,000 to 100,000 Daltons, said homopolymer being obtained from 2-acrylamido-2-methylpropanesulfonic acid in a salt-forming form containing impurities. Background Technology

[0002] High molecular weight anionic polyacrylamide (APAM) is commonly used in many applications due to its flocculating or thickening properties. In fact, these polymers are used in the following fields: oil and gas industry, hydraulic fracturing, papermaking processes, sludge dewatering, water treatment, construction, mining, cosmetic formulations, agriculture, textiles, and detergent formulations.

[0003] For example, the flocculation properties of these high molecular weight water-soluble synthetic polymers are used in the fields of water treatment / sludge dewatering. In fact, flocculation represents the process of particles aggregating into high molecular weight aggregates to produce rapid sedimentation, following an optional coagulation step in which colloidal particles of a given water (assimilated into spheres smaller than 1 micrometer) are destabilized.

[0004] The thickening properties of these polymers can be used in enhanced oil recovery (EOR) applications.

[0005] Most of the oil fields currently in operation are mature and have, in fact, begun or are about to decline in production. Compared to their initial production levels, these fields currently have an average recovery rate of approximately 15% to 35%. Therefore, they offer considerable production potential.

[0006] Typically, the recovery of crude oil contained in a mineral deposit is carried out in several stages.

[0007] Production is primarily a result of decompression of the natural energy of the fluids and rocks. At the end of this depletion phase, the amount of oil recovered on the surface averages about 5% to 15% of the initial reserves. Therefore, in the second step, it is necessary to employ techniques designed to enhance recovery by maintaining oilfield pressure.

[0008] The most common method is to inject water into the deposit through injection wells specifically designed for this purpose. This is called secondary recovery. This second stage stops when the water / oil ratio becomes too high, i.e., when the amount of water in the mixture produced by the production well is too high. Therefore, this secondary recovery can achieve an additional recovery rate of approximately 10 to 20% compared to the initial oil production.

[0009] Other technologies that can be used are classified as enhanced oil recovery (RAP or EOR, an abbreviation for "Enhanced Oil Recovery"). The goal is to recover 10% to 35% additional oil compared to the initial oil volume. Under the term "enhanced oil recovery," various thermal or non-thermal technologies (such as so-called electric, miscible, steam, or even chemical technologies) are known to improve the recovery of remaining oil (see "Oil & Gas Science and Technology"—IFP Review, Vol. 63 (2008), No. 1, pp. 9–19).

[0010] "Petroleum" refers to any type of oil, including light oil, heavy oil, and even bituminous oil. Oils are typically produced by the natural transformation of organic matter and consist of mixtures of hydrocarbons. In the description of the prior art or the present invention, the terms petroleum and oil are used to refer to the same material, except when referring to the composition of an emulsion or dispersion.

[0011] The efficiency of water injection for oil sweeping is typically improved by adding water-soluble high-molecular-weight synthetic polymers. The expected and proven benefits of using these polymers, through the "viscosification" of the injected water, are improved oil sweeping and a reduction in the viscosity contrast between fluids to control their mobility ratio in the oil field, thus enabling rapid and efficient oil recovery. These polymers increase the viscosity of the water.

[0012] These high molecular weight anionic polyacrylamides (APAMs) are most commonly used in powder form produced by gel polymerization, which requires very long dissolution times and complex and large equipment, such as PSUs (“Polymer Slicing Units”, document WO2008071808) and curing tanks. This is especially true when these APAM powders must be dissolved in cold water and / or brine. Incomplete dilution results in the need for excess polymer to achieve the desired properties (flocculation, thickening effects, etc.).

[0013] Besides increasing the viscosity of water, the polymer used must also possess good filterability. Polymers with poor filterability tend to clog underground formations, slowing down or even inhibiting oil production. However, filterability deteriorates as the molecular weight of the polymer increases. Therefore, there is a delicate trade-off between molecular weight and filterability.

[0014] Furthermore, these polymers are sensitive to free radical degradation once in solution, which causes their effectiveness to decline over time.

[0015] The production of oil and gas contained in unconventional reservoirs has been developed for many years, and it is necessary to open fractures in the reservoirs for economical production of oil and gas.

[0016] "Unconventional reservoirs" refer to mineral deposits that require specific extraction techniques because they do not exist in an aggregated form within porous and permeable rocks (see Bedrock Hydrocarbons in France Interim Report – CGIET n°2011-04-G – Ministry of ecology, sustainable development, transport and housing – April 2011). For unconventional natural gas, shale gas, coalbed methane, or tight gas may be mentioned. For unconventional oil, heavy oil, shale oil, or tight oil may be mentioned.

[0017] The reserves contained in unconventional reservoirs are enormous and widespread in previously untapped areas, such as bedrock hydrocarbons like shale, tight gas, and coal gas. In the United States, shale gas has been extensively developed and currently accounts for 46% of total natural gas production, compared to only 28% in 1998. Very extensive basins are known as the Barnett Shale, Ville Fayette Shale, Mowry Shale, Marcellus Shale, Utica Shale, and so on. Advances in drilling technology have made it possible to develop tight reservoirs.

[0018] Production technology has evolved from vertical wells to horizontal wells, reducing the number of production wells required, their footprint, and enabling better coverage of reservoir volumes for maximum natural gas recovery. However, insufficient permeability allows natural gas to easily migrate from bedrock to the well, thus hindering the economical and high-volume production of either natural gas or oil. Therefore, increasing permeability and the production surface through production enhancement operations, particularly hydraulic fracturing of the rock in contact with the well, is essential.

[0019] Hydraulic fracturing aims to create additional permeability and generate a larger production area for natural gas or oil. In reality, the low permeability of tight formations, natural barriers, and the watertightness of drilling operations severely limit production. Natural gas or oil contained in unconventional reservoirs cannot easily migrate from the rock to the well without increased production.

[0020] These hydraulic fracturing operations on horizontal wells began in the Appalachian Mountains in 1960 and have now been performed tens of thousands of times in the United States.

[0021] Reservoir design, modeling, drilling, cementing, and production enhancement technologies have become increasingly complex, and the use of equipment that allows these operations to be performed in less time and the results to be analyzed precisely.

[0022] These operations involve injecting water at high pressure and very high flow rates to create fractures perpendicular to the production well distribution. This is typically done in several stages to create fractures along the entire length of the horizontal well, allowing for the covering of the largest possible reservoir volume.

[0023] To keep these cracks open, proppant (sand, plastic material, or calibrated ceramics) is added to prevent the cracks from closing and to maintain the capillary action that occurs after injection stops.

[0024] Due to its low viscosity, water alone is insufficient for effective proppant placement, limiting its ability to hold proppant in the proper position within the fracture. To overcome this problem, fracturing fluids containing viscosity-enhancing compounds have been developed.

[0025] By definition, a compound is considered viscous when it increases the viscosity of the solution in which it is dissolved.

[0026] In addition to thickening properties, the compound must also possess specific rheological properties. Specifically, the polymer must be able to have a low viscosity so as not to interfere with the delivery and pumping of the proppant-containing fluid during the intense shearing process experienced during fracturing fluid injection. Once injected, the same compound must be able to generate sufficient viscosity to support the proppant and thus retain it within the fracture as shear forces decrease.

[0027] Therefore, the polymer must provide the solution with shear-thinning properties to have relatively low viscosity during injection (under high shear) and high viscosity when the shear decreases, in order to keep the proppant suspended at a level within the crack.

[0028] The viscoelastic properties of the polymer in solution should also be considered. SPE 147206 (Fracturing Fluid Comprised of Components Sourced Solely from the Food Industry Provides Superior Proppant Transport - David Loveless, Jeremy Holtsclaw, Rajesh Saini, Phil Harris and Jeff Fleming, SPE, Halliburton) describes this viscoelasticity and its importance in applications through visual observation in static or dynamic experiments, or even through rheological measurements (such as measuring viscosity and loss modulus (G' and G”), or measuring viscosity as a function of shear rate on a rheometer. Therefore, elastic properties will be beneficial in ensuring the transport and suspension of fracturing proppant.

[0029] Therefore, the choice of polymer is not obvious and requires in-depth rheological studies to obtain satisfactory results.

[0030] Among the thickening compounds in aqueous solutions that are part of the prior art, natural substances such as guar gum and its derivatives, such as hydroxypropyl guar gum (HPG) or carboxymethyl hydroxypropyl guar gum (CMHPG), and cellulose derivatives such as carboxymethyl cellulose or hydroxyethyl cellulose, may be mentioned. These compounds are specifically described in patents US4033415, US3888312, and US4801389. Recent advances in fracturing fluid performance are discussed in detail in SPE 152596 (Hydraulic Fracturing 101: What Every Representative, Environmentalist, Regulator, Reporter, Investor, University Researcher, Neighbor and Engineer Should Know About Estimating Frac Risk and Improving Frac Performance in Unconventional Gas and Oil Wells - George E. King, Apache Corporation).

[0031] However, these natural substances, especially guar gum derivatives, are also used in other applications, such as the food or textile industries, and the development of unconventional oil and gas resources competes with these other applications. This puts pressure on the availability of these products and leads to pricing issues.

[0032] Other compounds derived from petrochemicals can also possess thickening properties. Synthetic polymers can be mentioned. Poly(meth)acrylamide (possibly partially hydrolyzed) and poly(meth)acrylates and their copolymers are particularly known. These polymers increase viscosity due to their high molecular weight and interchain ionic repulsion.

[0033] These polymers are described in patents GB951147, US3727689, US3841402, or even US3938594. The mechanism for adjusting viscosity is related to the increase in hydrodynamic volume caused by intrachain repulsion, interchain entanglement, etc.

[0034] However, in the presence of high salinity or at high operating temperatures, these polymers do not generate strong entanglement and repulsion, resulting in a significant decrease in their viscosity, especially after the shearing during the pumping phase when injected into subsurface formations. Furthermore, these polymers typically do not possess sufficient viscoelastic properties to support the proppant in fracturing. The metering of these polymers must be increased to excess levels to achieve proppant suspension properties. Such metering levels are economically infeasible.

[0035] The polymer used to provide thickening properties can also advantageously be a friction reducer, which allows for a reduction in pressure drop in turbulent environments and a significant increase in flow rate at the same power and pipe diameter. Summary of the Invention

[0036] The applicant has surprisingly discovered that when a water-soluble anionic polymer P2 is prepared by polymerization of at least one anionic water-soluble monomer in the presence of a water-soluble homopolymer of 2-acrylamido-2-methylpropanesulfonic acid in a salt-forming form with a weight average molecular weight of 5,000 to 100,000 Daltons, it overcomes the problems of dissolution and sensitivity to free radical degradation. The water-soluble P1 polymer is prepared from AMPS (2-acrylamido-2-methylpropanesulfonic acid) in a salt-forming form and contains impurities.

[0037] In fact, the P2 polymer in the composition dissolves rapidly, especially in cold water and brine. This is particularly true when the composition is in the form of a solid composition (e.g., powder) or a suspension (e.g., an aqueous or oily particulate multiphase suspension). Introducing polymer P1 into the polymerization feed of the P2 polymer improves the dissolution of the P2 polymer, which allows for a smaller size of the equipment used for its implementation (reduced curing time), a more concentrated solution in polymer P2, and allows the P2 polymer to dissolve completely before its use. This is accompanied by improved application performance of polymer P2 while reducing the amount of polymer P2 used. Therefore, the carbon footprint associated with the use of the P2 polymer is reduced (rapid dissolution, less energy required for its dissolution, and a more concentrated solution).

[0038] Furthermore, polymer compositions containing P2 polymers increase the number of polymer chains per kilogram, and these chains, once in solution, protect the higher-quality APAM (anionic polyacrylamide P2) polymer chains from free radical degradation through a sacrificial effect. Therefore, the properties of P2 polymers are maintained for a longer period during use.

[0039] The anionic water-soluble P2 polymer of the present invention has improved properties, such as dissolution time, filterability, friction reduction and improved iron (ferrous and / or ferric) stability, and is particularly suitable for enhancing oil or gas recovery technologies.

[0040] More specifically, the P1 homopolymer added to the polymerization feed of the anionic P2 polymer is obtained from 2-acrylamido-2-methylpropanesulfonic acid in a salt form. This salt form is formed from 2-acrylamido-2-methylpropanesulfonic acid. This anionic monomer is not purified at the end of its manufacturing process: it is typically obtained via the Ritter reaction, or as a residue or waste product from the purification process of 2-acrylamido-2-methylpropanesulfonic acid.

[0041] The polymerization of this impure salt-forming form of 2-acrylamido-2-methylpropanesulfonic acid is preferably carried out without a transfer agent. Therefore, the P1 homopolymer (hereinafter referred to as the polymer) is usually phosphorus-free because the transfer agent is usually a phosphorus-containing compound, such as sodium hypophosphite.

[0042] According to the present invention, the P1 polymer can have linear, branched, "star" (i.e., star-shaped), "comb" (i.e., comb-shaped), and / or dendritic shapes. Preferably, it has a linear structure.

[0043] More specifically, the present invention relates to polymer compositions comprising a water-soluble P2 anionic polymer. The P2 polymer is obtained by free radical polymerization of at least one anionic monomer in the presence of a water-soluble P1 homopolymer with a weight-average molecular weight of 5,000 to 100,000 Daltons, said water-soluble P1 homopolymer being prepared from 2-acrylamido-2-methylpropanesulfonic acid in salt form in the presence of 200 to 20,000 ppm by weight of 2-methyl-2-propenesulfonic acid in salt form (before P2) (ppm is expressed as a weight of 2-acrylamido-2-methylpropanesulfonic acid in salt form).

[0044] Polymer compositions containing water-soluble P2 anionic polymers can be in the form of solutions (e.g., aqueous solutions), emulsions (e.g., water-in-oil emulsions), solid compositions (e.g., powders), or suspensions (e.g., aqueous suspensions). The form of the polymer composition may depend on the polymerization technique used to form the P2 polymer: gel polymerization; precipitation polymerization; emulsion polymerization (aqueous or reverse); suspension polymerization; reactive extrusion polymerization; water-in-water polymerization; and / or micellar polymerization. Preferred polymer compositions are in powder form and obtained by gel polymerization.

[0045] As used herein, the term "water-soluble polymer" refers to a polymer that, when stirred at 25°C for 4 hours, yields a product at a concentration of 20 g / L. -1 When a polymer is dissolved in deionized water at a concentration of [amount], it produces an aqueous solution without insoluble particles.

[0046] The term "polymer" refers to both homopolymers and copolymers of at least two different monomers.

[0047] Homopolymers comprise only one monomer. For example, in the context of this invention, AMPS homopolymers in salt form do not include AMPS in acid form.

[0048] Anionic polymers are polymers with anionic total charge. They contain anionic monomers and may optionally contain nonionic, cationic, or zwitterionic monomers.

[0049] The numerical range includes a lower limit and an upper limit. Therefore, the numerical ranges "between 0.1 and 1.0" and "0.1 to 1" include the values ​​0.1 and 1.0.

[0050] "A and / or B" means "choose from the group consisting of A, B and their mixtures", that is: A or B, or A and B.

[0051] According to the present invention, the weight-average molecular weight of the water-soluble P1 and P2 polymers is determined by measuring their intrinsic viscosity. Intrinsic viscosity can be measured by methods known to those skilled in the art, and in particular, can be calculated graphically from specific viscosity values ​​at different concentrations. This graphical method involves plotting the specific viscosity value (on the y-axis) as a function of concentration (on the x-axis) and extrapolating the curve to zero concentration. The intrinsic viscosity value is read on the y-axis or using the least squares method. The molecular weight can then be determined using the Mark-Houwink equation:

[0052] [η]=KM α ,in:

[0053] [η] represents the intrinsic viscosity of the polymer as determined by solution viscosity measurement.

[0054] K represents an empirical constant.

[0055] M represents the molecular weight of the polymer.

[0056] α represents the Mark-Houwink coefficient.

[0057] K and α depend on the specific polymer-solvent system. Tables known to those skilled in the art provide values ​​for α and K based on the polymer-solvent system.

[0058] The weight-average molecular weight of the P1 polymer is preferably 5,000 to 100,000 Daltons, more preferably 5,000 to 80,000 Daltons, and even more preferably 10,000 to 60,000 Daltons.

[0059] The weight-average molecular weight of the P2 polymer is preferably greater than 100,000 Daltons and less than or equal to 40 million Daltons, more preferably 1 million to 40 million Daltons, and even more preferably 1 million to 30 million Daltons.

[0060] The P1 polymer was advantageously obtained by free radical polymerization of 2-acrylamido-2-methylpropanesulfonic acid in aqueous solution in a salt-forming form, a method known to those skilled in the art.

[0061] The preferred Ritter method, which makes the production of 2-acrylamido-2-methylpropanesulfonic acid possible, results in the formation of impurities such as 2-methyl-2-propenyl-sulfonic acid and 2-methylene-1,3-propene disulfonic acid. Since the salt form of 2-acrylamido-2-methylpropanesulfonic acid used for P1 polymerization typically originates from the Ritter method without any purification, or from the washings of the purification process, it contains significant amounts of the aforementioned impurities in their salt form.

[0062] Preferably, the salt-formed 2-acrylamido-2-methylpropanesulfonic acid used to prepare homopolymer P1 contains 300 to 10,000 ppm of the salt-formed 2-methyl-2-propenyl-sulfonic acid. Therefore, homopolymer P1 is advantageously prepared in the presence of 300 to 10,000 ppm of the salt-formed 2-methyl-2-propenylsulfonic acid.

[0063] Preferably, the 2-acrylamido-2-methylpropanesulfonic acid used to prepare the P1 homopolymer, independently or not independently, contains 300 to 10,000 ppm by weight of the 2-methylene-1,3-propene disulfonic acid in its 2-methylene form. Therefore, the P1 homopolymer is advantageously prepared in the presence of 300 to 10,000 ppm of the 2-methyl-2-propenesulfonic acid in its 2-methylene form.

[0064] The salt form of 2-acrylamido-2-methylpropanesulfonic acid is advantageously identical to that of the aforementioned impurities (2-methyl-2-propenylsulfonic acid and 2-methylene-1,3-propenedisulfonic acid in salt form) for these three salts. It is typically an alkali metal salt selected from sodium, lithium, and potassium salts and / or an alkaline earth metal salt selected from magnesium, calcium, and / or an ammonium salt.

[0065] Preferably, the salt forms of 2-acrylamido-2-methylpropanesulfonic acid and 2-methyl-2-propenylsulfonic acid, and the salt form of 2-methylene-1,3-propene disulfonic acid (if present), are sodium salts.

[0066] P2 polymer is an anionic polymer obtained by free radical polymerization of at least one anionic monomer.

[0067] Preferably, the anionic monomer of the P2 polymer is selected from the group consisting of: acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, acrylamidodecanoic acid, 3-acrylamido-3-methylbutyric acid, maleic anhydride, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), vinyl sulfonic acid, vinyl phosphonic acid, allyl sulfonic acid, methyl allyl sulfonic acid, 2-methyl methacrylate sulfonyl ethyl ester, methyl methacrylate sulfonyl propionyl ester, acrylate sulfonyl propionyl ester, allyl phosphonic acid, styrene sulfonic acid, 2-acrylamido-2-methylpropane disulfonic acid, and water-soluble salts of these monomers, such as their alkali metal salts, alkaline earth metal salts, or ammonium salts, and mixtures thereof. Preferably, the anionic monomer is acrylic acid in salt form (advantageously sodium acrylate) or 2-acrylamido-2-methylpropanesulfonic acid in salt form (advantageously sodium 2-acrylamido-2-methylpropanesulfonate).

[0068] In addition to anionic monomers, polymer P2 may also contain nonionic monomers selected from the group consisting of: acrylamide, methacrylamide, N-alkylacrylamide, N-alkylmethylacrylamide, N,N-dialkylacrylamide, N,N-dialkylmethylacrylamide, alkoxylated acrylates, alkoxylated methacrylates, N-vinylpyridine, N-vinylpyrrolidone, hydroxyalkyl acrylates, hydroxyalkyl methacrylates, N-vinylformamide, and mixtures thereof, wherein the alkyl group is straight-chain or branched (preferably straight-chain) and is C1-C3. Preferably, the nonionic monomer is acrylamide.

[0069] In addition to anionic monomers and optionally nonionic monomers, monomers with hydrophobic characteristics can also be used to prepare P2 polymers. They are preferably selected from the group consisting of: (meth)acrylates having propoxylated, ethoxylated, ethoxylated, and propoxylated alkyl or arylalkyl chains; (meth)acrylamide derivatives having propoxylated, ethoxylated, or ethoxylated and propoxylated alkyl or arylalkyl chains; alkylaryl sulfonates; and disubstituted amides having two propoxylated, ethoxylated, or ethoxylated and propoxylated alkyl or arylalkyl chains of (meth)acrylamide; and mixtures thereof. In this list, the alkyl chain (straight or branched) has at least 4 carbon atoms, typically up to 8 carbon atoms, and the arylalkyl or alkylaryl chain has at least 7 carbon atoms, typically up to 15 carbon atoms.

[0070] Advantageously, the P2 polymer does not contain cationic monomers and / or zwitterionic monomers.

[0071] According to one specific implementation, the water-soluble P2 polymer may contain at least one LCST group.

[0072] Based on general knowledge of those skilled in the art, the LCST group corresponds to a group whose solubility in water at a given concentration changes as a function of salinity above a certain temperature. This is a group with a thermal transition temperature, indicating a lack of affinity for the solvent medium. This lack of affinity for the solvent leads to turbidity or loss of transparency, which can be due to precipitation, aggregation, gelation, or thickening of the medium. This lowest transition temperature is called "LCST" (an acronym for "Lowest Critical Solution Temperature"). The thermal transition temperature for each group concentration is observed at the LCST. It is above the LCST, i.e., the lowest point of the curve. Below this temperature, the polymer is soluble in water; above this temperature, the polymer loses its solubility in water.

[0073] According to one particular embodiment, the water-soluble P2 polymer may contain at least one UCST group.

[0074] Based on general knowledge of those skilled in the art, the UCST group corresponds to a group whose solubility in water at a given concentration changes below a certain temperature and is a function of salinity. This is a group with a cooling transition temperature, indicating a lack of affinity for the solvent medium. This lack of affinity for the solvent leads to turbidity or loss of transparency, which can be due to precipitation, aggregation, gelation, or thickening of the medium. This highest transition temperature is called "UCST" (an acronym for "Highest Critical Solution Temperature"). For each group concentration below UCST, a cooling transition temperature is observed. It is below UCST, i.e., the highest point of the curve. Above this temperature, the polymer is soluble in water; below this temperature, the polymer loses its solubility in water.

[0075] According to the present invention, the P2 polymer can have linear, branched, "star" (i.e., star-shaped), "comb" (i.e., comb-shaped), and / or dendritic structures. These structures can be obtained by selecting an initiator, a transfer agent (if present) (not preferred), a radical polymerization technique such as RAFT (reversible addition-fragmentation chain transfer), NMP (nitrogen oxide-controlled polymerization), or ATRP (atom transfer radical polymerization), and the introduction and concentration of the structural monomer.

[0076] According to the invention, the P2 polymer is advantageously linear or structured. "Structured polymer" refers to a nonlinear polymer with side chains so that when the polymer dissolves in water, it acquires a strongly entangled state, resulting in very high low-gradient viscosity. However, the structured polymer according to the invention remains water-soluble.

[0077] Water-soluble polymer P2 can also be structured using the following substances:

[0078] - At least one structural agent, which may be advantageously selected from the group consisting of polyene-bonded unsaturated monomers (i.e. having at least two unsaturated functional groups), such as vinyl, allyl, acrylic and epoxy functional groups;

[0079] Examples of possible names include methylenebisacrylamide (MBA), triallylamine, tetraallyl ammonium chloride, or 1,2-dihydroxyethylenebis-(N-acrylamide), and / or

[0080] - Macromolecular initiators, such as polyperoxides, polyazo compounds, and polytransfer agents such as polythiols and polyols, and / or

[0081] - Functionalized polysaccharides.

[0082] The amount of branching / crosslinking agent in the monomer mixture is advantageously less than 4% by weight, more advantageously less than 1%, and even more preferably less than 0.5% relative to the total monomer content. According to one specific embodiment, it can be at least 0.00001% by weight relative to the total monomer content.

[0083] Typically, P2 water-soluble polymers do not require the development of specific polymerization methods. In fact, they can be obtained using any polymerization technique known to those skilled in the art. Specifically, it can be solution polymerization; gel polymerization; precipitation polymerization; emulsion polymerization (aqueous or reverse); suspension polymerization; reactive extrusion polymerization; water-in-water polymerization; or micellar polymerization.

[0084] Advantageously, the P2 polymer is obtained by gel or reverse emulsion polymerization methods known to those skilled in the art.

[0085] Polymer P1 is added before the polymerization of the monomer begins, advantageously simultaneously with the anionic monomer and any other monomers, and usually before the addition of any initiator (azo compound, peroxide and / or redox system).

[0086] In a preferred embodiment, polymer P2 is polymerized from 5 to 100 mol% anionic monomers and 0 to 95 mol% nonionic monomers, preferably 10 to 50 mol% anionic monomers and 50 to 90 mol% nonionic monomers. Advantageously, polymer P2 consists of 5 to 100 mol% anionic monomers and 0 to 95 mol% nonionic monomers. If applicable, the total amount of monomers constitutes 100 mol% of the monomers in the presence of other monomers (hydrophobic, cationic, zwitterionic, LCST or UCST monomers).

[0087] Advantageously, the polymer composition contains 0.01 to 5.0% by weight of polymer P1 relative to the dry weight of the polymer composition, more preferably 0.05 to 3% by weight, and even more preferably 0.1 to 2% by weight.

[0088] Another aspect of the invention relates to the use of polymer compositions comprising anionic P2 polymers in the following fields: hydrocarbon (oil and / or natural gas) recovery; drilling and cementing; production enhancement of oil and gas wells (oil and / or natural gas), such as hydraulic fracturing, homogenization, and diversion; water treatment, such as in open, closed, or semi-closed loops; fermentation and mold treatment; sludge treatment; papermaking; construction; wood treatment; treatment of hydraulic compositions (concrete, cement, mortar, and aggregates); mining; cosmetic formulations; detergent formulations; textile manufacturing; battery component manufacturing; geothermal energy; sanitary pad manufacturing; or agriculture.

[0089] The polymer compositions according to the invention are preferably used as flocculants, coagulants, adhesives, fixatives, viscosity reducers, thickeners, absorbents, friction reducers, draining agents, drainage agents, filler retainers, dehydrating agents, regulators, stabilizers, fixatives, film-forming agents, sizing agents, superplasticizers, clay inhibitors, or dispersants.

[0090] The present invention also relates to a method for enhancing hydrocarbon (oil and / or natural gas) recovery by probing underground formations, comprising the following steps:

[0091] a. An injection fluid is prepared from the polymer composition according to the invention with water or brine.

[0092] b. Inject the fluid into the underground formation.

[0093] c. Use injected fluid to scan underground strata.

[0094] d. Harvesting aqueous mixtures of hydrocarbons (oil and / or natural gas).

[0095] According to the invention, the injected fluid advantageously contains 10 ppm to 15,000 ppm of water-soluble polymer P2 relative to the weight of the injected fluid, more advantageously 50 ppm to 10,000 ppm, and even more advantageously 100 ppm to 5,000 ppm.

[0096] The term "filtration quotient" is used herein to refer to a test used to determine the performance of polymer compositions according to the invention under low-permeability conditions in subsurface formations (or reservoirs). This test involves measuring the time required for a given volume / concentration of solution (injected fluid) to pass through a filter. FR typically compares the filterability of two consecutive equivalent volumes of solution, representing the tendency of the solution to clog the filter. A lower FR indicates better performance.

[0097] The test used to determine FR involves measuring the time it takes for a given volume of solution containing 1000 ppm of active polymer (in a polymer composition containing P2) to flow through a filter. The solution is placed in a pressurized cell at a pressure of two bar, and the filter has a diameter of 47 mm and a specified pore size. Typically, filters with pore sizes of 1.2 μm, 3 μm, 5 μm, or 10 μm are used to measure FR.

[0098] Therefore, 100ml (t) was obtained by measurement. 100ml ), 200ml (t) 200ml ) and 300ml (t 300ml The time required for filtrate filtration is then used to determine FR, expressed as:

[0099]

[0100] The time is accurate to 0.1 seconds.

[0101] Therefore, FR represents the ability of a polymer solution to clog two equivalent continuous volumes of a filter.

[0102] The final aspect of this invention relates to a method for hydraulically fracturing underground hydrocarbon (oil and / or natural gas) reservoirs, comprising the following steps:

[0103] a. An injection fluid is prepared from the polymer composition according to the invention, water or brine, and at least one proppant.

[0104] b. Inject the fluid into the underground reservoir and fracturing at least a portion of it to recover hydrocarbons (oil and / or some natural gas).

[0105] The proppant can be selected without limitation from sand, ceramics, bauxite, glass beads, and resin-impregnated sand. It preferably accounts for 0.5% to 40% of the weight of the injected fluid, more preferably 1% to 25%, and even more preferably 1.5% to 20%.

[0106] The injected fluid may include other compounds known to those skilled in the art (such as those summarized in document EPS 152596):

[0107] - Anti-swelling agents for clay, such as potassium chloride or choline chloride.

[0108] - Biocides to prevent the growth of bacteria, especially sulfate-reducing bacteria, which can form a sticky substance that reduces the surface area of ​​channels. Glutaraldehyde is the most widely used, followed by formaldehyde or isothiazolinone.

[0109] -Oxygen reducing agents, such as ammonium bisulfite, are used to prevent other components from being destroyed by oxidation and corrosion of the injection tube.

[0110] - Anti-corrosion additives, used to protect pipes from oxidation by residual oxygen, such as N,N-dimethylformamide.

[0111] - Lubricants, such as petroleum distillates

[0112] - Iron chelating agents, such as citric acid, EDTA, or phosphonates,

[0113] - Scale inhibitor products, such as phosphates, phosphonates, polyacrylates, or ethylene glycol.

[0114] According to another embodiment, the water-soluble P2 polymer in the fracturing fluid is in the form of an aqueous particulate multiphase suspension prior to being introduced into the fracturing fluid, comprising:

[0115] (i) 15 to 60% by weight of at least one polymer P2 in the form of solid particles with an average size of 5 to 500 μm;

[0116] (ii) 15 to 45% by weight of at least one alkali metal salt and / or at least one alkaline earth metal salt;

[0117] (iii) At least one thickener that is different from a water-soluble polymer;

[0118] (iv) at least 10% by weight of water; and

[0119] The suspension has a Brookfield viscosity of 500 to 20,000 cps and a density of 1.1 to 2 kg·L at 25°C. -1 .

[0120] According to another embodiment, the P2 water-soluble polymer is in the form of an oily particulate multiphase suspension before it is introduced into the fracturing fluid, comprising:

[0121] (v) 15 to 60% by weight of at least one P2 polymer in the form of solid particles with an average size of 5 to 500 μm;

[0122] (vi) 15 to 45% by weight of at least one alkali metal salt and / or at least one alkaline earth metal salt;

[0123] (vii) At least one thickener other than a water-soluble polymer;

[0124] (viii) At least 10% by weight of oil; and

[0125] The suspension has a Brookfield viscosity of 500 to 20,000 cps and a density of 0.6 to 1.4 kg·L at 25°C. -1 .

[0126] Brookfield viscosity was measured using a Brookfield viscometer equipped with an LV module. This module is capable of rotating at, for example, 30 rpm, and measurements are advantageously performed at 20°C.

[0127] In this invention, average size refers to the average diameter of the particles. An example of a device used to measure the average particle diameter, based on conventional techniques known to those skilled in the art, is the Mastersizer from Malvern Instruments.

[0128] Density was measured at 25°C and 1 atmosphere (i.e., 101,325 Pa).

[0129] Preferably, when the water-soluble polymer P2 is in a fracturing oilfield, its concentration in the injection fluid (fracturing fluid) is 0.005 to 5 pptg (“pounds per thousand gallons”; one pound represents 0.45359237 kg, and one gallon represents 3.78541 liters). Even more preferably, its concentration is 0.1 to 3 pptg.

[0130] The following examples illustrate the present invention but do not limit its scope. Detailed Implementation

[0131] Example 1: Synthesis of polymers P1a, P1b and P1c

[0132] 190g of deionized water was added to a 1-liter jacketed reactor equipped with a condenser and a stirrer, and heated to 80°C under a nitrogen atmosphere (nitrogen flow).

[0133] Sodium persulfate solution was prepared by dissolving 17 g of sodium persulfate in 100 g of deionized water in a dropping funnel. 690 g of a 50 wt% aqueous solution of the sodium salt of 2-acrylamido-2-methylpropanesulfonic acid (Na-AMPS) was added to a second dropping funnel. High-performance liquid chromatography (HPLC) analysis showed that the amount of 2-methyl-2-propenyl-sulfonic acid in sodium form was 1556 ppm (wt / Na-AMPS), and the amount of 2-methylene-1,3-propenedisulfonic acid in sodium form was 450 ppm (wt / Na-AMPS).

[0134] Sodium persulfate solution was added to the reactor over a 120-minute period, followed by the addition of a sodium salt solution of 2-acrylamido-2-methylpropanesulfonic acid over a 90-minute period. During the addition of these reagents, the reaction was continued for another 60 minutes (calculated after the addition of sodium persulfate), maintaining the reaction medium at 80°C. The resulting P1a polymer according to the invention has a weight-average molecular weight of 47,000 Daltons (determined by intrinsic viscosity).

[0135] The synthesis of polymer P1b was carried out using the same method as that used for polymer P1a, the only difference being that the polymerization temperature was maintained at 100°C. The resulting polymer P1b according to the invention has a weight-average molecular weight of 24,600 Daltons (determined by intrinsic viscosity).

[0136] The synthesis of polymer P1c was carried out using the same method as that used for polymer P1a, the only difference being that the salt form of 2-methylpropanesulfonic acid (Na-AMPS) contained 102 ppm of sodium salt form of 2-methyl-2-propenyl-sulfonic acid and 80 ppm of sodium salt form of 2-methylene-1,3-propene disulfonic acid. The resulting P1c polymer according to the invention has a weight-average molecular weight of 245,000 Daltons (determined by intrinsic viscosity).

[0137] All the P1 polymers described above are in aqueous solution form, with the sodium salt form of the 2-methylpropanesulfonic acid homopolymer having a concentration of 40% by weight in water.

[0138] Example 2: Polymer composition comprising the P2a and P2b polymers according to the present invention and the comparative P2c polymer Synthesis of (P2 polymer: acrylamide / sodium acrylate polymer)

[0139] Add 389g of deionized water, 102g of acrylic acid (90% by weight aqueous solution), 396g of acrylamide (50% by weight aqueous solution) and 16g of polymer P1a (40% by weight aqueous solution) to a 1000mL beaker.

[0140] The resulting solution was cooled to 5 to 10°C and neutralized with 113 g of a 50% by weight aqueous solution of sodium hydroxide (NaOH) while maintaining the temperature below 10°C. The solution was then transferred to an adiabatic polymerization reactor. Nitrogen bubbling was then performed for 30 minutes to remove all trace amounts of dissolved oxygen.

[0141] Then add the following substances to the reactor:

[0142] -0.45g 2,2'-azobisisobutyronitrile,

[0143] -1.5 mL of an aqueous solution of 2.5 g / L 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride.

[0144] -1.5 mL of 1 g / L sodium hypophosphite aqueous solution,

[0145] -1.5 mL of 1 g / L tert-butyl hydrogen peroxide aqueous solution,

[0146] -1.5 mL of 1 g / L ammonium sulfate and ferric(II) hexahydrate (molar salt) aqueous solution.

[0147] A few minutes later, nitrogen bubbling was stopped. The exothermic polymerization reaction proceeded for 4 hours to reach the peak temperature. At the end of this period, the obtained polymer gel was shredded, dried, and then ground again to obtain the P2a polymer of the present invention in powder form with a weight-average molecular weight of 24,230,600 Daltons (determined by intrinsic viscosity).

[0148] By applying the same method, but in the absence of polymer P1, polymer P2b was obtained. The weight-average molecular weight of the P2b polymer thus obtained according to the invention is equal to 24,320,500 Daltons (determined by intrinsic viscosity).

[0149] Using polymer P1c instead of polymer P1a, polymer P2c is obtained by applying the same method. The weight-average molecular weight of the P2c polymer obtained according to the invention is equal to 24,400,500 Daltons (determined by intrinsic viscosity).

[0150] Example 3: Polymers comprising the P2d and P2e polymers according to the present invention and the comparative polymers P2f and P2g. Synthesis of the composition (P2 polymer: sodium 2-acrylamido-2-methylpropanesulfonate homopolymer)

[0151] Add 584g of deionized water, 300g of sodium 2-acrylamido-2-methylpropanesulfonate (50% by weight aqueous solution), and 14g of polymer P1a (40% by weight aqueous solution) to a 1000mL beaker.

[0152] The resulting solution was cooled to 5 to 10°C and neutralized with 116 g of a 50% by weight aqueous solution of sodium hydroxide (NaOH) while maintaining the temperature below 10°C. The solution was then transferred to an adiabatic polymerization reactor. Nitrogen bubbling was then performed for 30 minutes to remove all trace amounts of dissolved oxygen.

[0153] Then add the following substances to the reactor:

[0154] -0.45g 2,2'-azobisisobutyronitrile,

[0155] -1.5 mL of an aqueous solution of 2.5 g / L 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride.

[0156] -1.5 mL of 1 g / L sodium hypophosphite aqueous solution,

[0157] -1.5 mL of 1 g / L tert-butyl hydrogen peroxide aqueous solution,

[0158] -1.5 mL of 1 g / L ammonium sulfate and ferric(II) hexahydrate (molar salt) aqueous solution.

[0159] A few minutes later, nitrogen bubbling was stopped. The exothermic polymerization reaction proceeded for 4 hours to reach the temperature peak. At the end of this period, the obtained polymer gel was shredded, dried, and then ground again to obtain the P2d polymer of the present invention in powder form with a weight-average molecular weight of 8,630,200 Daltons (determined by intrinsic viscosity).

[0160] Using polymer P1b instead of polymer P1a, polymer P2e was obtained by applying the same method. The weight-average molecular weight of the P2e polymer thus obtained in powder form is equal to 8,400,000 Daltons (determined by intrinsic viscosity).

[0161] Using polymer P1c instead of polymer P1a, polymer P3f was obtained by applying the same method. The weight-average molecular weight of P2f in powder form thus obtained is equal to 8,500,000 Daltons (determined by intrinsic viscosity).

[0162] By applying the same method, but in the absence of polymer P1, polymer P2g was obtained. The weight-average molecular weight of the comparative P2g polymer according to the invention, thus obtained in powder form, is equal to 8,230,100 Daltons (determined by intrinsic viscosity).

[0163] By applying the same method, but with the addition of 60g of polymer P1b, polymer P2g was obtained. The weight-average molecular weight of the P2g polymer according to the invention, thus obtained in powder form, is equal to 4,890,250 Daltons (determined by intrinsic viscosity).

[0164] Example 4: Polymer composition comprising polymer P2h according to the present invention and comparative polymers P2i and P2j Synthesis of (polymer P2: a terpolymer of acrylamide / sodium acrylate / sodium 2-acrylamido-2-methylpropanesulfonate)

[0165] Add 461g of deionized water, 105g of sodium 2-acrylamido-2-methylpropanesulfonate (50% by weight aqueous solution), 30g of acrylic acid (90% by weight aqueous solution), and 10g of polymer P1b (40% by weight aqueous solution) to a 1000mL beaker.

[0166] The resulting solution was cooled to 5 to 10°C and neutralized with 74 g of a 50% by weight aqueous solution of sodium hydroxide (NaOH) while maintaining the temperature below 10°C. The solution was then transferred to an adiabatic polymerization reactor. Nitrogen bubbling was then performed for 30 minutes to remove all trace amounts of dissolved oxygen.

[0167] Then add the following substances to the reactor:

[0168] -0.45g 2,2'-azobisisobutyronitrile,

[0169] -1.5 mL of an aqueous solution of 2.5 g / L 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride.

[0170] -1.5 mL of 1 g / L sodium hypophosphite aqueous solution,

[0171] -1.5 mL of 1 g / L tert-butyl hydrogen peroxide aqueous solution,

[0172] -1.5 mL of 1 g / L ammonium sulfate and ferric(II) hexahydrate (molar salt) aqueous solution.

[0173] A few minutes later, nitrogen bubbling was stopped. The exothermic polymerization reaction proceeded for 4 hours to reach the peak temperature. At the end of this period, the obtained polymer gel was shredded, dried, and then ground again to obtain the P2h polymer of the present invention in powder form with a weight-average molecular weight of 14,630,600 Daltons (determined by intrinsic viscosity).

[0174] By applying the same method, but in the absence of polymer P1, polymer P2i was obtained. The weight-average molecular weight of polymer P2i according to the invention, thus obtained in powder form, is equal to 14,780,500 Daltons (determined by intrinsic viscosity).

[0175] Polymer P1c was used instead of polymer P1a, and polymer P2j was obtained by applying the same method. The weight-average molecular weight of the obtained powdered polymer P2j was 14,000,800 Daltons (determined by intrinsic viscosity).

[0176] Example 5: Comparison of P2 polymer dissolution rates

[0177] A P2 polymer solution with an active concentration of 1000 ppm was prepared in deionized water or a brine solution containing water, 30,000 ppm NaCl, and 3000 ppm CaCl2·2H2O. The aqueous solution was stirred, and the powder was slowly introduced into a vortex formed by a magnetic rod. The time for complete dissolution of the polymer in the aqueous solution corresponded to the time when the polymer solution reached its maximum viscosity.

[0178] [Table 1]

[0179]

[0180] Example 6: Measurement of the chemical degradation resistance of P2 polymer solution

[0181] Chemical degradation resistance tests were conducted under aerobic conditions in the presence of different concentrations of iron(II) (2, 10, and 20 ppm) in a brine consisting of water, 37,000 ppm NaCl, 5,000 ppm Na2SO4, and 200 ppm NaHCO3 (ppm is expressed as a weight relative to the weight of the brine). The results obtained after the P2 polymer solution was exposed to the contaminant (iron(II)) for 24 hours are shown in Table 2.

[0182] [Table 2]

[0183]

[0184] Example 7: Measurement of the filtration quotient of P2 polymer solution

[0185] A P2 polymer solution with an active concentration of 1000 ppm was prepared in a brine containing water, 30,000 ppm NaCl, and 3,000 ppm CaCl2·2H2O (ppm is expressed as a weight relative to the weight of the brine). The filtration quotient (FR) was measured on a filter with a pore size of 3 μm, representing low-permeability sediment. The results are shown in Table 3.

[0186] [Table 3]

[0187] polymer Molecular weight (Daltons) Filter Manufacturer (FR) P2a (This invention) 24,230 600 1.1 P2b (comparison) 24,320 500 1.17 P2c (comparison) 24,400 500 1.22 P2d (This invention) 8,630 200 1.09 P2e (This invention) 8,400 000 1.05 P2f (comparison) 8,500,000 1.19 P2g (comparison) 8,230,100 1.21 P2h (This invention) 14,630,600 1.09 P2i (comparison) 14,780 500 1.23 P2j (comparison) 14,000,800 1.22

[0188] Example 8: Friction Reduction Test of Flow Loop

[0189] Under stirring, the P2 polymer was dissolved at a concentration of 10,000 ppm in a brine solution composed of water, 85 g of sodium chloride (NaCl), and 33.1 g of calcium chloride (CaCl2·2H2O) per liter. The resulting polymer-saline solution was then injected into the recirculated brine solution for flow loop testing at a concentration of 0.05 pptg. The flow loop consisted of a recirculation loop with an inner diameter of 1.27 cm, a pump, and multiple pressure sensors installed along the recirculation loop. The flow loop was pre-filled with 20 liters of brine and recirculated at a rate of 24 gallons per minute. The percentage of friction reduction was determined by measuring the pressure change within the flow loop. The polymer's properties were measured based on the maximum friction reduction obtained and the time required to achieve that maximum value.

[0190] When the maximum friction reduction is high and the time required to achieve that maximum friction reduction is short, the product efficiency is higher.

[0191] [Table 4]

[0192]

[0193]

Claims

1. A polymer composition comprising a water-soluble anionic P2 polymer, said water-soluble anionic P2 polymer being obtained by free radical polymerization of at least one anionic monomer in the presence of a water-soluble P1 homopolymer with a weight-average molecular weight of 5,000 to 100,000 Daltons. The water-soluble anionic P2 polymer has a weight-average molecular weight greater than 100,000 Daltons and less than or equal to 40 million Daltons. The water-soluble P1 homopolymer was prepared from 2-acrylamido-2-methylpropanesulfonic acid in salt form in the presence of 200 to 20,000 ppm by weight of 2-methyl-2-propenesulfonic acid in salt form.

2. The polymer composition according to claim 1, characterized in that The water-soluble P1 homopolymer was prepared in the presence of 300 to 10,000 ppm of 2-methyl-2-propenylsulfonic acid in its salt-forming form.

3. The polymer composition according to any one of claims 1 or 2, characterized in that, The water-soluble P1 homopolymer was prepared in the presence of 300 to 10,000 ppm by weight of 2-methylene-1,3-propylene disulfonic acid in its salt-forming form.

4. The polymer composition according to claim 1 or 2, characterized in that, The salt forms of 2-acrylamido-2-methylpropanesulfonic acid and 2-methyl-2-propenylsulfonic acid, and the salt form of 2-methylene-1,3-propenedisulfonic acid if present, are sodium salts.

5. The polymer composition according to claim 1 or 2, characterized in that, The water-soluble anionic P2 polymer has a weight-average molecular weight of 1 million to 40 million Daltons.

6. The polymer composition according to claim 1 or 2, characterized in that, The anionic monomers of the water-soluble anionic P2 polymer are selected from the group consisting of: acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, acrylamidodecanoic acid, 3-acrylamido-3-methylbutyric acid, maleic anhydride, 2-acrylamido-2-methylpropanesulfonic acid (ATBS), vinyl sulfonic acid, vinyl phosphonic acid, allyl sulfonic acid, methyl allyl sulfonic acid, 2-methyl methacrylate sulfoethyl ester, methyl methacrylate sulfopropyl ester, acrylate sulfopropyl ester, allyl phosphonic acid, styrene sulfonic acid, 2-acrylamido-2-methylpropane disulfonic acid, and water-soluble salts of these monomers, and mixtures thereof.

7. The polymer composition according to claim 1 or 2, characterized in that, The water-soluble anionic P2 polymer contains 10 to 100 mol% anionic monomers and 0 to 90 mol% nonionic monomers.

8. The polymer composition according to claim 1 or 2, characterized in that, It contains 0.01 to 5.0% by weight of water-soluble homopolymer P1.

9. Use of the polymer composition according to any one of claims 1 to 8 in the fields selected from: water treatment; sludge treatment; papermaking; construction; wood processing; mining; cosmetic formulations; detergent formulations; textile manufacturing; battery component manufacturing; geothermal energy; sanitary pad manufacturing; and agriculture.

10. Use of the polymer composition according to any one of claims 1 to 8 as a flocculant, coagulant, binder, fixative, viscosity reducer, thickener, absorbent, friction reducer, drainage agent, filler retainer, dehydrating agent, regulator, stabilizer, film-forming agent, sizing agent, superplasticizer, clay inhibitor, or dispersant.

11. A method for enhancing oil and / or natural gas recovery by scavenging underground formations, comprising the following steps: a. An injection fluid is prepared from the polymer composition according to any one of claims 1 to 8 with water or brine. b. Inject the fluid into the underground formation. c. Use injected fluid to scan underground strata. d. Harvesting water-bearing mixtures of oil and / or natural gas.

12. A method for hydraulic fracturing underground oil and / or natural gas reservoirs, comprising the following steps: a. An injection fluid is prepared from the polymer composition according to any one of claims 1 to 8, water or brine, and at least one proppant. b. Inject the fluid into the underground reservoir and fracture at least a portion of it to recover oil and / or natural gas.

Citation Information

Patent Citations

  • Well fracturing

    GB951147A

  • Hydraulic fracturing

    US3727689A

  • Fracturing with radiation-induced polymers

    US3841402A

  • Method and compositions for fracturing well formations

    US3888312A

  • Fracturing fluid

    US3938594A